Technology of increase in efficiency of development of coordination abilities and technical and tactical actions of athletes in free-style - Qaxramonovich, A. S. (European Journal of Research and Reflection in Educational Sciences, 2019)
In work the technology of increase in efficiency of development of coordination abilities and technical and tactical actions of athletes in free-style wrestling with use of the tool technique is developed and experimentally proved.